The Visual Elements of Building Façade Forming Image of Jalan Besar Ijen as a Historic Area - Kartika Lestari Gladysia; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Jalan Besar Ijen is the most famous area in Malang City for its beautiful environments and buildings. This area is one of the historical areas of the Dutch Colonial people which has a row of residential buildings in colonial architectural style. Seeing the condition of Jalan Besar Ijen, there are few research and books stating that the image of Jalan Besar Ijen has changed as a historic area due to land conversion and rapid investment in Malang. Where changes occur mainly in the building facade. One way that can be done is to maintain the visual elements of the building facade. This study aims to discover how does the visual elements of building facades affect the image of Jalan Besar Ijen  as a historic area based on public perception. This type of research is a descriptive study with a quantitative approach. The results of this study indicate that the visual elements of the building facade have a 45.1% influence on the image of the historic area on Jalan Besar Ijen. And there are 4 variables that have a significant influence, namely shape, color, decoration on the building facade, and architectural style.